Enterprise-Based Empowerment Strategy for Santri in the Agribusiness Sector in Creating an Influential (Infa’) Generation - Achmad Zam Zami; Sofuan Jauhari (Universitas Muhammadiyah Ponorogo, 2026)
Public skepticism about the relevance of Islamic boarding school graduates in the modern job market creates a gap between the traditional curriculum and the demands of economic independence. An applied educational transformation is urgently needed so that students become not only religious figures but also strong economic actors. This study aims to analyze strategies for empowering students based on agribusiness entrepreneurship and describe the profile of the